KOMITE NASIONAL INDONESIA PUSAT (KNIP) SEBUAH ANOMALI SUPRASTRUKTUR NEGARA PADA TAHUN 1945 - UNGGUL SUGIHARTO, UNGGUL SUGIHARTO (Program Magister Ilmu Politik, Universitas Diponegoro, 2010)
AbstractPolicies in a very strategic and important country, in providing good governance and thesource of many aspects of people's lives. This is due to that country's policy will extend to all sectorsin a variety of community life. Policy benchmark various possibilities for the utilization of resources -economic and political sources of law in one state.Another value is that the impact of the breadth of state policies, state policy making is an importantsource of attraction interests an actor to play therein. Thus, within certain limits of state policy can beseen who exactly was behind it.The last condition indicates that the policy of the state can show the power of multilateral actors orinstitutions of the world that work across sectors and countries, or who became known as the MultiNational Corporation (MNC). In other aspects of institutions like the World Bank, IMF or world financialgroup is another example of the importance of ideology, to fit in a single country. The effect is theinclusion of understanding which then referred to as Neo-Liberalism, in which various interests andaspects of play and injected.Key words : State, Policies and Neo-Liberalism